Forming of practical translation skills of economists by means of information technologies - Pradivliannyi, M. H. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper considers the problem dealing with application of information technologies in the training process for advanced foreign languages training of economists. The paper suggests new approach to classes’ organization in practical translation skills acquirement, using new forms of training organization based on information technologies.